THE PRESENTATION OF GENDER ROLES IN AND OUTSIDE FICTION, AND THE REBELLIOUS SPIRIT OF WOMEN ARTISTS IN VIRGINIA WOOLF’S TO THE LIGHTHOUSE AND A ROOM OF ONE’S OWN* - Limanta, Liem Satya (k@ta: A Biannual Publication on the Study of Language and Literature, 2005)
This paper tries to portray the roles of men and women in and outside fiction as seen in Virginia Woolf’s To the Lighthouse and A Room of One’s Own. In both works, Woolf described vividly how women were often kept in the unfortunate and inferior positions by men and the patriarchal system they made. However, women did not always accept the marginalization without reserve. I will show that women’s rebellious and unconsenting spirit is represented especially by women artists in and outside fiction.